First 41 UMPSA students awarded PASKAM Second Lieutenant Rank - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 9 August 2025 – A total of 41 cadets from the Malaysian Maritime Cadet Corps (PASKAM) Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) successfully completed the first training series and received the rank insignia of Second Lieutenant in a full ceremonial event held at the Dewan Astaka, UMPSA Gambang Campus today.